Impact of Coal Mining on Groundwater Quality and Human Health: A Case Study - Swastik Choubay; Ram Chandra Chaurasia (International Journal of Science, Strategic Management and Technology, 2026)
Groundwater resources in coal mining regions are increasingly threatened by intensive mining activities that alter natural hydrogeochemical conditions and facilitate the mobilization of heavy metals into aquifer systems. This study evaluates the groundwater quality and associated human health risks in the Sohagpur Coalfield, Shahdol District, Madhya Pradesh, India, a major coal-producing region of the Son Valley Basin. The assessment integrates hydrogeological perspectives with physicochemical and heavy metal analyses to investigate the influence of mining operations on groundwater quality. Human health risk assessment was performed following the United States Environmental Protection Agency (USEPA) methodology by estimating the Average Daily Dose (ADD), Hazard Quotient (HQ), Hazard Index (HI), and Carcinogenic Risk (CR) through the oral ingestion pathway. The findings reveal considerable spatial variability in groundwater chemistry, primarily controlled by geological formations, hydrogeochemical processes, mine water discharge, acid mine drainage, overburden leachates, and waste disposal practices. Elevated concentrations of selected heavy metals were observed in groundwater samples collected near mining activities, resulting in increased non-carcinogenic and carcinogenic risks at several locations. While many sampling sites exhibited HQ and HI values within acceptable limits, certain sites exceeded the recommended thresholds, indicating potential health risks associated with long-term consumption of untreated groundwater. Carcinogenic metals, particularly arsenic, chromium, cadmium, and nickel, contributed significantly to lifetime cancer risk where their concentrations surpassed guideline values. The study highlights the necessity for continuous groundwater quality monitoring, scientific mine waste management, periodic health risk assessment, and implementation of sustainable groundwater protection strategies in mining regions. The outcomes provide valuable information for environmental managers, policymakers, and mining authorities to support evidence-based groundwater management and safeguard public health in coal mining areas.